The pupil as an indicator of unconscious memory: Introducing the pupil priming effect. (5th February 2015) - Gomes, Carlos Alexandre; Montaldi, Daniela; Mayes, Andrew
Abstract We explored whether object behavioral priming and pupil changes occur in the absence of recognition memory. Experiment 1 found behavioral priming for unrecognized objects (Ms) regardless of whether they had been encoded perceptually or conceptually. Using the same perceptual encoding task, Experiment 2 showed greater pupil dilation for Ms than for correct rejections of unstudied objects (CRs) when reaction times were matched. In Experiment 3, there was relatively less pupil dilation for Ms than for similarly matched CRs when objects had been encoded conceptually. Mean/peak pupil dilation for CRs, but not Ms, increased in Experiment 3, in which novelty expectation was also reduced, and the pupillary time course for both Ms and CRs was distinct in the two experiments. These findings indicate that both behavioral and pupil memory occur for studied, but unrecognized stimuli, and suggest that encoding and novelty expectation modulate pupillary memory responses.